Application of Modified-ACLS Electrodes on Low-platinum PEFCs. (14th September 2015) - Mei, Wu; Fukazawa, Taishi; Yang, Tianyi; Yoshinaga, Norihiro; Kanai, Yuta
Abstract : Alternating catalyst layer structure (ACLS) is a promising low-platinum technology for the PEFC application. This report discusses modification of ACLS in recent years, focusing on the enhancement of oxygen reduction reaction activity (ORR) and load cycle durability. For modified-ACLS electrodes (M-electrodes), single cell measurement showed about 6 times ORR specific activity compared with commercial Pt3 Co/C. Excellent durability of M-electrodes was confirmed even with a Pt loading of 0.025 mgPt/cm 2, revealing the possibility of their application as ultra-low-platinum PEFC anodes.